Comparison of the theory of planned behavior and health belief model in predicting physical activity among cardiac patients - Low, Han Loong (2015)
Multiple health behavior theories that aim to predict behavior exist in current literature. However, studies involving these theories often do not make empirical comparisons between models, resulting in a fragmented understanding of determinants of health behavior. The present study compared the predictive utility of the Theory of Planned Behavior (TPB) with the Health Belief Model (HBM) on physical activity behavior. Fifty-one patients undergoing a community-based cardiac rehabilitation program in Singapore were recruited for this study. Both the Theory of Planned Behavior and the Health Belief Model were each found to significantly predict physical activity behavior. Multiple regression analyses revealed that the strongest predictors were subjective norm and perceived behavioral control from the TPB, and perceived susceptibility and severity from the HBM. Together, the current study illustrated that the two models possess different strengths that may be exploited in various contexts; and has contributed to a more cohesive understanding of health behavioral theories.